Establishing a TAVR Program in a Non-ECMO Center: Anesthetic Considerations and Safety Workflow - Defitra Nanda Sasmita; Anas Alatas (Riviera Publishing, 2026)
Optimal anesthetic management during the initiation of a transcatheter aortic valve replacement (TAVR) program in centers without extracorporeal membrane oxygenation (ECMO) capability remains underexplored. This case report describes anesthetic considerations and contingency planning for establishing a new TAVR program in a cardiac catheterization laboratory. A 66-year-old male patient with severe aortic stenosis (valve area: 0.74 cm²; mean gradient: 43.89 mmHg; ejection fraction: 47%), coronary artery disease, congestive heart failure (NYHA class II), and chronic kidney disease stage III underwent transfemoral TAVR under general anesthesia as the inaugural procedure of the program. The procedure was performed in a cardiac catheterization laboratory without on-site ECMO support, with cardiac surgery standby and cardiopulmonary bypass equipment prepared in an adjacent operating room. Hemodynamic management during rapid ventricular pacing (180 beats/min for 10 seconds during balloon valvuloplasty and 120 beats/min during valve deployment) included preemptive phenylephrine boluses (total dose: 2 mg) and cautious crystalloid administration (500 mL). A 27 mm VitaFlow valve was successfully deployed. Post-deployment transesophageal echocardiography demonstrated mild paravalvular leak without intravalvular regurgitation or valve dislodgement. The patient was discharged on postoperative day 3 without complications. General anesthesia supported by structured hemodynamic management protocols and clearly defined cardiac surgery contingency planning enabled safe TAVR implementation during program initiation in a non-ECMO center. This case provides a practical framework for institutions establishing similar programs without immediate ECMO capability.